Valuasi Ekonomi Ekowisata Kawasan Ekosistem Esensial (KEE) Pantai Taman Kili-Kili Kabupaten Trenggalek - Ihsannudin Ihsannudin; Amanatuz Zuhriyah; Aji Silwa Al Masih (Program Studi Agribisnis, 2022)
Ecotourism KEE Kili-Kili beach, located in Trenggalek Regency, is rich in biodiversity and natural beauty. Valuation is needed to determine the use value or benefits of resources and the environment. Economic value of resources that offer natural beauty, in general, are non-market (does not have a market price) because they are public goods. This study aims to estimate the potential economic value of KEE ecotourism at Taman Kili-Kili beach, Trenggalek Regency. This study is a quantitative study with multiple linear regression analysis to determine the factors that influence the number of tourist visits. Meanwhile, to find out the economic value, the individual travel cost method (ITCM) is used. The results showed that only the motivation variable had a significant effect on the number of visits variable. The economic potential of ecotourism KEE at Taman Kili-Kili beach reaches Rp. 34,580,440,612/year. The magnitude of the value of the economic benefits of natural resources and the ecotourism environment of the Taman Kili-Kili KEE coast is expected by managers and related stakeholders to improve ecotourism management by adding tourist facilities and attractions to provide more satisfaction for visitors. In addition, the improvement of the access road to the location is very necessary in order to provide convenience and comfort in reaching the location.